Respuesta :
Answer:
[tex]a=[2q^{2}r][/tex]
[tex]b=[3s^{2}t][/tex]
Step-by-step explanation:
we have
[tex]8q^{6}r^{3}+27s^{6}t^{3}[/tex]
we know that
[tex]8q^{6}r^{3}=(2^{3})(q^{2})^{3}r^{3}=[2q^{2}r]^{3}[/tex]
[tex]27s^{6}t^{3}=(3^{3})(s^{2})^{3}t^{3}=[3s^{2}t]^{3}[/tex]
therefore
[tex]a=[2q^{2}r][/tex]
[tex]b=[3s^{2}t][/tex]
substitute
[tex]a^{3} +b^{3}=(a+b)(a^{2} -ab+b^{2})[/tex]
[tex][2q^{2}r]^{3} +[3s^{2}t]^{3}=([2q^{2}r]+[3s^{2}t])([2q^{2}r]^{2} -[2q^{2}r][3s^{2}t]+[3s^{2}t]^{2})[/tex]
[tex][2q^{2}r]^{3} +[3s^{2}t]^{3}=([2q^{2}r]+[3s^{2}t])([4q^{4}r^{2}] -6[q^{2}r][s^{2}t]+[9s^{4}t^{2}])[/tex]